The Constitutional Court Verdict Constribution towards International Civil Law Development in Indonesia - Havez, Muhammad; Rehulina, Rehulina; Azizah, Siti; Hakim, Amran; Al Hamid, Bayu (LPPM Universitas Lampung, 2022)
This research will be assessing the Constitutional Court verdicts related to issues of International Private Law. The assessment itself will be conducted through descriptive qualitative research method using socio-legal approach. The data collection method was carried out qualitatively, namely: through literature studies and focus group discussions. Then, the results of the evaluation will show the hypothesis of the level of development in the field of Civil law International law in Indonesia based on the legal considerations of the Constitutional Court and their impact of these decisions. Where since 2013, Constitutional Court had repeatedly contributed to the development of International Private Law in Indonesia. Although Constitutional Court remain their stands on limiting the rights on land ownership only apply for Indonesian citizen. But by 2015, through Constitutional Court Verdict No. 69/PUU-XIII/2015, the Constitutional Court determined that prenuptial agreement could be hold to secure the interest of each couple within mix marriage.